Fever pitch - Hornby, Nick. (London : Penguin, 2000)
Recreates the fever pitch of football fans in Great Britain, and describes how football has played a defining role in thousands of young men's coming-of-age stories.
Keywords: Football -- Great Britain; Soccer -- Great Britain